Pembelajaran Bahasa Inggris Melalui Lagu pada Anak Usia Dini (THUFULA, 2013)
This article describes the advantages and the examples of song to support English language learning process. Moreover, this article explains the position of English language in Indonesia and the characteristic of children as foreign language learners. Children have unique characteristics that could be employed for the supporting factors and disadvantaging factors of foreign language learning process. They need to move and be able to concentrate for a short term, learn through experiences, have less ability to control and plan their activities, not fear to do some mistakes or take risks, not really pay attention to their shelves or their actions, pay attention to the language purpose, and posses limited experiences in their lives. Songs are learning resources that have so many advantages, including linguistics resource, affective/psychological resource, and cognitive resource. Songs can be good learning sources as teaching media for English language class.